Development of a kinetic model for hydrogen production from phenol over Ni-Co/ZrO2 catalyst - Nabgan, W. (Elsevier Ltd, 2016)
Study on the kinetics of steam reforming of phenol was performed over a Ni-Co/ZrO2 catalyst. It provides basis for the optimization of reactors design for better phenol conversion and H2 yield. An effect of temperature, catalyst weight, phenol concentrations in the feed, and the volumetric feed flow rate on the catalyst activity and reaction rate have been investigated in detail and were explored through experiment. At the present reaction conditions, the reaction was found to be free from mass and heat transfer limitations. The reaction order was determined through a power law kinetic model based on the Langmuir-Hinshelwood-Hougen-Watson (LHHW) and Eley-Rideal (ER) postulations. The kinetic constants and activation energy were arrived at through a non-linear regression approach. It has been found that the reaction rate depends strongly on phenol concentration. The phenol conversion process was found to have activation energy 102.27 J/mol. 6 models were developed with 2 being eliminated due to predictive efficiency. From mechanistic point of view, both of the phenol and steam behaved based on non-dissociative adsorption.